Structural design optimization of a high speed synchronous reluctance machine - Di Nardo, Mauro; Lo Calzo, Giovanni; Galea, Michael; Gerada, C. (2016)
Synchronous reluctance machines, including the permanent magnet assisted variants are competitive motor topologies if the application requires high efficiency and a cost effective solution with a high flux weakening capability. However, increasing speeds incur challenging design and development decisions, in order to find an optimal solution between the machine performance and its structural integrity. In this paper, a comprehensive design procedure for such machines is presented, where a 5kW, 80000 rpm synchronous reluctance machine is considered. The proposed strategy consists of a two-step proce-dure in which the electromagnetic and structural designs have been properly decoupled dividing the design space in two subsets. Each subset mainly affects the electromagnetic or the structural performances. Several structural design optimizations have been performed with the aim of finding the optimal trade-off between the rotor geometrical complexity (i.e. computational time) and the electromagnetic performance. The results shown in this paper validate the proposed design strategy which can be used as general guidelines on the structural design of synchronous reluctance machines.